Process Research on Optimization of the Surface Phosphating Quality of CHQ ML20MnTiB by Orthogonal Test - HOU Kai-yuan, ZHAO Guang-xing, DU Ying-qi, ZHANG Lei, GUO Li-qiang, JING Shuang-hui (Cailiao Baohu)
Aiming at improving the surface phosphating quality of CHQ ML20MnTiB and meeting to the needs of customers for large deformation multi station high speed cold processing molding technology, the effects of different pickling and drawing processes on phosphating film weight, SEM morphology and composition of alloy steel wire ML20MnTiB were studied by orthogonal test.Results showed that under the conditions of the second-time wire extraction without acid pickling, chemetel phosphating and fine extraction deformation by 10% control, the obtained surface phosphating skin film possessed the maximum weight, the highest phosphating beneficial components and the optimal micro morphology, which could satisfy the requirements of cold processing molding technology.